Hybrid and Model-Based Iterative Reconstruction Influences the Volumetry of Visceral and Subcutaneous Adipose Tissue on Ultra-Low-Dose CT - Lambert, Lukas; Novák, Matěj; Siklova, Michaela; Krauzova, Eva; Stich, Vladimir; Burgetova, Andrea (Obesity, 2020)
OBJECTIVE: The aim of this study was to compare three different reconstruction algorithms for the volumetry of the visceral adipose tissue (VAT) and subcutaneous adipose tissue (SAT) on ultra-low-dose computed tomography (CT) images. METHODS: Thirty-seven male patients underwent ultra-low-dose CT at the level of the fourth lumbar vertebra (22.5 mm in z-axis). The acquisitions were reconstructed in 5-mm slices with 50% overlap using filtered back projection (FBP), hybrid iterative reconstruction (HIR), and iterative model-based reconstruction (IMR) techniques. The volume of VAT and SAT was measured using an interactive seed-growing segmentation and by thresholding (-30 to -190 HU). RESULTS: The volume of SAT measured by the interactive method was smaller in FBP compared with both HIR (P = 0.0011) and IMR (P = 0.0034), and the volume of VAT was greater in IMR compared with HIR (P = 0.0253) or FBP (P = 0.0065). Using the thresholding method, IMR volumes of VAT were greater compared with HIR (P < 0.0001), and volumes of SAT were greater compared with both HIR and FBP (both P ≤ 0.0001). The VAT to SAT ratio was greater in IMR compared with HIR or FBP (both P < 0.0001). CONCLUSIONS: There are significant differences among FBP, HIR, and IMR in the volumetry of SAT and VAT, their ratios, and attenuation measured on ultra-low-dose images.
Keywords: algoritmy; dospělí; Humans; lidé; podkožní tuk; mužské pohlaví; Male; Case-Control Studies; Algorithms; Subcutaneous Fat; studie případů a kontrol; Adult; Tomography, X-Ray Computed; počítačová rentgenová tomografie